2014
DOI: 10.1155/2014/252851
|View full text |Cite
|
Sign up to set email alerts
|

Growth of ZnO Nanorods on Stainless Steel Wire Using Chemical Vapour Deposition and Their Photocatalytic Activity

Abstract: The photodegradation efficiency of ZnO nanoparticles in removal of organic pollutants deteriorates over time as a high percentage of the nanoparticles can be drained away by water during the wastewater treatment. This problem can be solved by growing the ZnO nanorods on stainless steel wire. In this work, ZnO nanorods were successfully grown on stainless steel wire by chemical vapour deposition. The SAED analysis indicates that ZnO nanorod is a single crystal and is preferentially grown in [0001] direction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Indeed a clear well-established Zn 2p 3/2 peak is observed at 202nd and 270th ALD cycles on fluorocarbon/Si. This peak is observed at a binding energy value of 1022.12 eV and corresponds to the Zn–O bond . These results show excellent correlation with all the characterization results provided so far.…”
Section: Resultssupporting
confidence: 88%
“…Indeed a clear well-established Zn 2p 3/2 peak is observed at 202nd and 270th ALD cycles on fluorocarbon/Si. This peak is observed at a binding energy value of 1022.12 eV and corresponds to the Zn–O bond . These results show excellent correlation with all the characterization results provided so far.…”
Section: Resultssupporting
confidence: 88%
“…In AOP, highly reactive radicals are generated that convert the organic pollutants into less hazardous products having potential to oxidize them. Many nanomaterials such as metal oxide semiconductors including zinc oxide (ZnO) (Aziz et al 2014;Chan et al 2013;Daneshvar et al 2007;Hong et al 2009;Xie et al 2011), titanium dioxide (TiO 2 ) (Chan et al 2014;Esfahani et al 2012;Smijs and Pavel 2011), Copper oxide (CuO) (Mehr et al 2018), Tungsten Oxide (WO 3 ) (Tahir et al 2018b) have been reported as wide band gap photocatalyst for degradation of pollutants under the Ultraviolet (UV) light. As the solar light spectrum contains 45% of visible light and less than 10% of UV light (Chan et al 2014).…”
Section: Introductionmentioning
confidence: 99%